University Students’ Perspectives on Online Learning via the Microsoft Teams Platform - Stramkale, Ligita (Journal of Education Culture and Society, 2023)
Aim. The aim of the study was to determine students’ perspectives on collaboration, the study process and motivation while using the Microsoft Teams (MS Teams) platform for online learning. Methods. The study involved 124 (N=124) students of 1st-level higher professional education, bachelor’s and master’s study programmes, who studied in full-time and part-time study forms. The study addressed three research questions. RQ1: What are students’ perspectives on collaboration while learning online via the MS Teams platform and whether their opinions depend on age, study level, form of study and course? RQ2: What are students’ perspectives on the study process via the MS Teams platform, and whether their views influenced by age, study level, study form and course? RQ3: What is the students’ motivation to study online on the MS Teams platform, and does it depend on age, level of study, study form and course? The study used statistical Package for Social Sciences (SPSS 22.0) for quantitative data analysis. Results. The students believe that they can easily collaborate on the MS Teams platform. Students’ perspectives on collaboration are not related to study form, the level of study, or the course, but in some instances, are connected with the age of the students. The majority of students evaluate the study process on MS Teams positively. Their views are not related to study form, the course or the age, but in some cases, connected with the level of study. The students’ motivation to study online using MS Teams is grown by reducing time consumption, the convenience of learning in their environment and the ability to complete the tasks easier, but their motivation could decrease because this form of study is less exciting compared with face-to-face and does not create satisfaction. Conclusion. The study concluded that: Firstly, with increasing age, student satisfaction with mutual collaboration on the MS Team platform declines, secondly students of the lower-level programme believe they are more likely to ask questions, receive feedback, and understand information than those who study in the higher-level programme, thirdly young students and those who study in the lower-level programme find learning online via the MS Teams platform more exciting than older students and those who study in the higher-level programme. Further research needs to find out why students of the lower-level study programmes believe they are more likely to ask questions, receive feedback and understand information while learning online on MS Teams, and it is also essential to investigate what factors determine whether or not studies are exciting.